A Mixed Method Framework for Evaluating Video Digital Libraries - Albertson, Dan (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
This paper generalizes the methodology of a comprehensive interactive video retrieval study in order to propose a framework that can be applicable for evaluating digital libraries. The presented framework depicts a set of evaluations and other methodological consideration deemed to be significant to digital libraries.  Quantitative methods described here measure outcomes and factors related to users and their action, perceptions, and experiences.  Factors for which to compare and contrast these measures across the framework are also outlined. Qualitative measures, which are not common to larger interactive retrieval studies, are also proposed including technique and pertinent themes relevant to evaluations aimed at obtaining deeper understanding of users and digital libraries.